Quantifying human presence in a heterogeneous urban landscape. (19th August 2019) - Corsini, Michela; Marrot, Pascal; Szulkin, Marta
Abstract: Humans are a keystone species in urban ecosystems. Although the impact of human activities is increasingly reported in behavioral and evolutionary ecology, little is known about the effects of physical human presence per se . Of particular relevance is the extent to which human presence (sometimes referred to as human disturbance), is repeatable across the urban mosaic over time. We quantified human presence at fixed locations—here in a 15-m radius of great tit nestboxes—within six urban and suburban study sites. While overall human presence did not differ between urban sites, it was significantly higher than in the suburban village. Moreover, considerable variance between fixed locations was observed within each site. We reported overall high repeatability of human presence for all sites (0.57 < R < 0.88, mean: 0.76, median: 0.77). We further simulated datasets of human presence made of an increasing number of counts, and demonstrated that 10 counts of human presence (each 30 s long) made at each fixed location can generate a highly reliable indicator of human presence ( R ≥ 0.6) for any urban site. We thus confirm that human presence is repeatable across the urban mosaic, thereby offering consistent cues to urban wildlife of human presence or absence in space and time. Importantly, our approach of human presence quantification allows for an effort-efficient approach to understand the effects of physical human presence at designated temporal timeframes, thereby allowing to reliably test the effects of human presence on the behavior and ecology of urban wildlife. Abstract : The bark of a dog, the run of a jogger, the speed of a bike: all these sounds and sights are visible in the city and are directly linked to the number of humans. We developed a method to quantify human abundance at specific timeframes and locations within a given study site. Human abundance was highly repeatable over time in sites within the city, but less so in a suburban site situated 20 km apart.